2021
DOI: 10.3389/fmolb.2021.791597
|View full text |Cite
|
Sign up to set email alerts
|

ARMC Subfamily: Structures, Functions, Evolutions, Interactions, and Diseases

Abstract: Armadillo repeat-containing proteins (ARMCs) are widely distributed in eukaryotes and have important influences on cell adhesion, signal transduction, mitochondrial function regulation, tumorigenesis, and other processes. These proteins share a similar domain consisting of tandem repeats approximately 42 amino acids in length, and this domain constitutes a substantial platform for the binding between ARMCs and other proteins. An ARMC subfamily, including ARMC1∼10, ARMC12, and ARMCX1∼6, has received increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…Furthermore, we have demonstrated that PRDM9 methylates CTNNBL1 at K394 both in vitro and in cells. Lysine 394 resides within an ARM repeat region of CTNNBL1; ARM repeats form an α-superhelix, providing a platform for protein interactions, including activation or degradation of the target protein ( 32 ). In the case of the related protein β-catenin, regulation of lysine methylation within an ARM repeat region was shown to regulate protein stability ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have demonstrated that PRDM9 methylates CTNNBL1 at K394 both in vitro and in cells. Lysine 394 resides within an ARM repeat region of CTNNBL1; ARM repeats form an α-superhelix, providing a platform for protein interactions, including activation or degradation of the target protein ( 32 ). In the case of the related protein β-catenin, regulation of lysine methylation within an ARM repeat region was shown to regulate protein stability ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have demonstrated that PRDM9 methylates recombinant CTNNBL1 protein at K394. Lysine 394 resides within an ARM repeat region of CTNNBL1; ARM repeats form an α-superhelix, providing a platform for protein interactions, including activation or degradation of the target protein (32). In the case of the related protein β-catenin, regulation of lysine methylation within an ARM repeat region was shown to regulate protein stability (24).…”
Section: Discussionmentioning
confidence: 99%
“…Some α/β hydrolases have been involved in salt and cold tolerance in plants and microorganisms, including yeasts ( Brody et al, 2001 ; Takahashi et al, 2006 ; Liu et al, 2014 ; Wu et al, 2020 ). ARMCs form a large family of enzymes primarily characterized in multicellular organisms (e.g., in plants) and exhibiting very versatile and fundamental functions, including response to stress, such as osmotic ( Kojima et al, 2013 ; Sharma and Pandey, 2015 ; Huang et al, 2021 ). MFS is a ubiquitous transporter superfamily whose members have a broad spectrum of substrates, such as inorganic and amino acids, nucleosides, lipids, and short peptides ( Yan, 2015 ); some members of MFS are involved in resistance to oxidative stress and fungicides in fungal pathogen Alternaria alternata ( Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%